2023
DOI: 10.1002/adhm.202203201
|View full text |Cite|
|
Sign up to set email alerts
|

Injectable Antibacterial Hydrogel with Asiaticoside‐Loaded Liposomes and Ultrafine Silver Nanosilver Particles Promotes Healing of Burn‐Infected Wounds

Abstract: Post‐injury infection and wound healing are recurrent daily life problems. Therefore, the necessity of developing a biomaterial with antibacterial and wound‐healing properties is paramount. Based on the special porous structure of hydrogel, this work modifies recombinant collagen and quaternary ammonium chitosan and fused them with silver nanoparticles (Ag@mental‐organic framework (Ag@MOF)) with antibacterial properties, and asiaticoside‐loaded liposomes (Lip@AS) with anti‐inflammatory/vascularization effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
3
7
0
Order By: Relevance
“…Asiaticoside (Asia) is a triterpenoid component extracted from a plant called Centella asiatica. It has been proven to be widely used as a drug in fields such as antioxidant, anti-inflammatory activity, immune regulation, and burn wound healing . Moreover, it has the ability to enhance collagen protein synthesis in vitro and promote extracellular matrix accumulation in vivo. , However, Asia has almost no antibacterial properties, which cannot provide assistance for the healing process of a burn wound.…”
Section: Introductionmentioning
confidence: 99%
“…Asiaticoside (Asia) is a triterpenoid component extracted from a plant called Centella asiatica. It has been proven to be widely used as a drug in fields such as antioxidant, anti-inflammatory activity, immune regulation, and burn wound healing . Moreover, it has the ability to enhance collagen protein synthesis in vitro and promote extracellular matrix accumulation in vivo. , However, Asia has almost no antibacterial properties, which cannot provide assistance for the healing process of a burn wound.…”
Section: Introductionmentioning
confidence: 99%
“…For example, One study focused on the development of protein/chitosan hydrogels enriched with AgNPs, aimed at enhancing the healing process of burn wounds. 7 Another research effort involved the creation of AgNP-loaded polymer hydrogels through in situ graft copolymerization, with a goal to expedite wound healing. 8 Therefore, the functionalized hydrogel synthesized by AgNPs and natural polymer materials has the characteristics of environmental friendliness, high safety, and adaptability to various needs of the human body, which makes it an ideal medical material.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Silver nanoparticles (AgNPs) have attracted increasing attention in biological applications such as wound healing due to their green, safe, and broad-spectrum antibacterial effects and have been used to develop functionalized hydrogels. For example, One study focused on the development of protein/chitosan hydrogels enriched with AgNPs, aimed at enhancing the healing process of burn wounds . Another research effort involved the creation of AgNP-loaded polymer hydrogels through in situ graft copolymerization, with a goal to expedite wound healing .…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen therapy has emerged clinically, which focuses on the use of enzymes to catalyze the production of hydroxyl free radicals, superoxide, and other reactive oxygen species from hydrogen peroxide (H 2 O 2 ) to combat bacteria. Although many proteases, such as the natural peroxidases and oxidases, are used to catalyze the production of reactive oxygen species, natural proteases suffer from denaturation and loss of enzymatic activity due to their ease of digestion. As a result, researches have focused on nanoparticles (NPs) known as nanoenzymes, which have catalytic properties comparable to those of natural proteases. Metal and metal oxides, in particular, are especially promising for biomedical applications due to their superior catalytic capabilities and innate antibacterial activity. For example, Wang et al investigated the effect of ultrasmall Au/Pt NCs@GO X clusterzyme on enhancing cascade catalyzed antibiofilm resistance . Yang et al found that hollow Cu 2 MoS 4 nanospheres could be used to treat implant infections and achieve immuomodulation .…”
Section: Introductionmentioning
confidence: 99%